The visual guidance of dance Images in humanities documentaries - Yu, Kun; Yaakup, Hani Salwah; Syed Zainudin, Sharifah Sofiah; Mohammad Razi, Siti Aishah (Redfame Publishing, 2023)
Do communicators' emotional expressions in dance-themed visual expressions in humanities documentaries depend on the visual guidance of dance camera language? There is limited information related to humanities documentaries with dance as a theme in the literature. The purpose of this study was to examine the effect of the creator's visual guidance on an audience's perception of dance images. Based on a humanities documentary’s overall tone, the communicator selected appropriate dance sequences and dance clips and recorded them from a dancer's point of view to capture an image's moral expression and bring the humanities documentary to a climax. The study explored whether an audience’s perspective of visual information from a dance in which the dance body language is guided by a video varies from that perceived when watching the dance in the past. This analysis opens up new avenues for video display and dance representation for the expression of dance video, to satisfy an audience's sense of observation and communicate an emotional expression.